The role of epithelial-mesenchymal transition in the pathogenesis of various diseases: A review - Mariam A. Vardanyan; Ellina I. Pilyugina; Alina S. Badlaeva; Vladimir D. Chuprynin; Natalya A. Buralkina (ZAO "Consilium Medicum", 2024)
Epithelial-mesenchymal transition (EMT) is a cellular process in which epithelial cells acquire the phenotype and properties of mesenchymal cells. This process plays a large and important role in the progression of various diseases, in the launch of trigger mechanisms at various stages of development, both in men and women, of different age categories. The conducted analysis of literary data allows us to conclude that the triggering factors of EMT in the pathogenesis of various diseases are similar. The impact on the molecular biological targets of EMT will prevent the formation of diseases at early stages. This fact will contribute to the search for targeted drugs for the treatment of such patients.